Output-volatility reducing effect of automatic stabilizers: Evidence from nine EMU member states - Hüseyin Şen; Ayşe Kaya (ZBW – Leibniz Information Centre for Economics, 2019)
In this paper, we explore the output-volatility reducing role of automatic stabilizers in the nine EMU member states comprising Austria, Finland, France, Germany, Ireland, Italy, Portugal, the Netherlands, and Spain for the period 1995-2017. Overall, the empirical results obtained by using the Pooled Mean Group estimator proposed by Pesaran et al. (1999) suggest that automatic stabilizers deliver a significant counter-effect on output volatility measured by the real GDP per capita volatility in the short run. More specifically, output-volatility responses to automatic stabilizers by a reduction between -1.2 and -9.7 percentage points depending on the proxy measure used for automatic stabilizers. However, the output-volatility reducing effect of automatic stabilizers is statistically insignificant in the long run. The results support the view that automatic stabilizers are an important fiscal mechanism for the short-run output stabilization, but their output-volatility offsetting role is largely subject to what the proxy measures are used for automatic stabilizers.
Keywords: E31; E32; E62; 330; Automatic stabilizers; Fiscal policy; PMG estimator; EMU member states